Folk, dannelse og styreform: En anmeldelse af Ove Korsgaard, Kampen om folket (2004) - Wåhlin, Vagn (Grundtvig-studier, 2004)
Folk, dannelse og styreform: En anmeldelse af Ove Korsgaard “ Kampen om folket” (2004).[People, Education and Government: A Review of Ove Korsgaard ‘ The Battle over the People’ (2004) ]By Vagn Wåhlin Ove Korsgaard, Kampen om folket. Et dannelsesperspektiv på dansk historie gennem 500 år [The Battle over the People: A Perspective of Education through 500 years of Danish History] (Gyldendal, Copenhagen, 2004), 672 p.From the day of its publication, Ove Korsgaard’s brilliant dissertation has had much influence on the Danish understanding of Denmark’s 500-year process of establishing the concepts of individual, society, people, and democracy. The author distinguishes between demos, the general population of the state, and ethnos, that part of the population which has inherited and accepted rights and obligations as far as and beyond a constitution and written laws. These latter are folket, the people.This primary division leads to a similar distinction between state and nation as well as a parallel distinction in government between representative government and democratic, self-organization of the citizens. A special focus of the book is the interaction and mutual dependency of the specified categories in an historical perspective of change from a late feudal society to a modem democratic welfare state. Essential institutions in this long societal process have been (a) the Lutheran Church; (b) from 1814, the municipal local schools for all, including girls; (c), for centuries, the patriarchal household; and (d) the rising centralized power of king and state. These four institutions formed the ideological and practical base of society until, through the slow effect of the Enlightenment, the individual and the people as such, within a national and democratic framework, took over in the period 1870-1900 and became the ideological basis of society with special and defined rights and duties attaching to every adult male and, from 1920, female. After the pre-1814 ethnic and cultural Danish-Norwegian-German conglomerate state finally broke down with the loss (1814) of Norway to Sweden and (1864) the duchies of Schleswig and Holstein to Pmssia, Denmark became the most ethnically and linguistically homogeneous state of Europe. Not until then could the ethnic concept of ‘the p e o p l folket, finally take over the indisputable role as the rock of the Danish society - a role which was further strengthened by the German occupation of Denmark 1940-45.Before 1870, 75% of all cultivated land was worked by the owners of medium-sized family farms, and some 75% of the population made their living in the agrarian sector of society. Agriculture produced the necessary surplus to pay for Denmark’s imports. From 1870, when the farmers began to organize effectively, they gained a higher economic, cultural and political status in Danish class-structured society which they were able to maintain for a hundred years. Up to 1870-90 Copenhagen was the only urban-industrial centre of any great significance, and from the 1890s the organized industrial capital and its workforce rose in influence; but not until the 1960s and 70s did these succeed in outdoing the fundamental influence of the agrarian sector on a national scale. Regrettably, this economic perception of the lower middle-class appearance of Danish society has been under evaluated in Korsgaard’s book, and the reader may thus miss a vital factor in the development of the democratic understanding of the Danish ethnos.The labour unions and the labour movement in politics never became revolutionary to any great extent and from 1916-29 renounced any such tendency and won a national position as a trustworthy partner in a coalition with other political and social forces. They graduated from expressing purely class interests to representing the whole population of Denmark. This led to the formation of a general welfare state for all after the Second World War. All political parties and national movements took part in building a welfare provision from cradle to grave, covering 80-90% of the population, which led to an embracing of both ethnos and demos.From the post-industrial and post-modern society of 1970 until today no leading classes in coalition with other groups have been able to formulate a common ideology and political guidelines for the future. So the Danes collectively are insecure about the future, and divided as to whether they want globalisation, Muslim newcomers, the E Uconstitution etc.All in all, this book is a fascinating and well-written contribution to the current debate: Where do we come from? Who are we? And where are we heading?